A cross-sectional study of risk factors associated with sarcopenia in patients with metabolic dysfunction-associated steatotic liver disease - Amer, Johnny; Abdoh, Qusay; Salous, Zaina; Alsoud, Eithar Abu; AbuBaker, Sama; Salhab, Ahmad; Badrasawi, Manal (Frontiers in Medicine, 2025)
BackgroundMetabolic dysfunction-associated steatotic liver disease (MASLD) is a chronic liver disease linked to several adverse health consequences that include metabolic disturbances affecting skeletal muscle. Sarcopenia, characterized by skeletal muscle loss, is commonly observed in individuals with MASLD. Our study aimed to identify modifiable lifestyle factors associated with sarcopenia in patients with MASLD.MethodsThis study was a cross-sectional study that was conducted in three clinics in Nablus. A total of 162 adults diagnosed with MASLD were recruited for the study. The patients were interviewed and instructed to provide the necessary information, such as sociodemographic factors, medical and surgical history, lifestyle information, MASLD-related data, and nutritional and functional status. Sarcopenia was defined using the Foundation for the National Institutes of Health (FNIH) criteria, which includes the weight-adjusted skeletal muscle index (wSMI) with the cut-off scores (male subjects: 35.7% and female subjects: 30.7%). Statistical analysis was conducted using SPSS v.21. A chi-squared or independent samples t-test was utilized to identify the factors linked to sarcopenia in the study sample.ResultsOur data found that 44% of MASLD patients had sarcopenia. This condition was significantly associated with female gender (p < 0.0001), older age (p < 0.0001), presence of chronic diseases (p < 0.035), and medication use (p < 0.05). Regarding nutritional factors, sarcopenia had a significant association with obesity, a higher body fat percentage, a high waist-to-hip ratio, a low mid-upper arm circumference, and a reduced calf circumference (p < 0.001). Sarcopenic individuals often exhibit reduced handgrip strength. Lifestyle factors such as a history of smoking and the type of smoking were found to be positively associated with sarcopenia (p < 0.0001).ConclusionSarcopenia was prevalent in the study population and was linked to modifiable risk factors that can be managed to reduce its progression. Future research using different study designs, such as longitudinal design, is recommended to identify the determinants of sarcopenia. Intervention studies are also required to improve the nutritional and functional status of MASLD patients.